The Angelology of Sergius Bulgakov - Maciej Raczyński-Rożek (Polonia Sacra)
Contemporary angelology is primarily an apologetic response to the negation of the existence of the angelic reality by liberal Protestantism. Bulgakov’s teaching about angels, on the other hand, arose as an indispensable part of the theological system. The orthodox author defines angels as created ideas of reality. As with Plato, every thing has its own idea, so with Bulgakov it has its own angel. The angels are therefore closely related to the earthly world and are its guardians, leading the world to the realization of the meaning given to it. Angels are also closely related to God because it is their nature to be filled with divine life. Thus, they constitute “Jacob’s ladder” — the reality that connects the world with God.